Enhancing participatory evaluation in a humanitarian aid project. (April 2017) - Rossignoli, Cristiano M.; Giani, Alberto; Di Iacovo, Francesco; Moruzzo, Roberta; Scarpellini, Paola
This article examines participatory evaluation of humanitarian aid projects in post-conflict contexts, through the presentation of a particular case: the evaluation of a project supporting herders and Bedouin communities breeding small ruminants in the Gaza Strip. The article analyses the current situation in the Gaza Strip, a unique humanitarian context, in order to gain insight into the value of participatory evaluation in post-conflict settings. The article analyses the participatory evaluation in order to understand how participation functions, what lessons can be learned and what outcomes can be generated. Finally, this experience demonstrates how participatory evaluation can work effectively in humanitarian settings despite the obvious constraints of conflict and post-conflict settings. Whilst participatory evaluation contributes to improving humanitarian-aid interventions, a more structural approach to participation is needed to achieve concrete and durable results.